Predictive Maintenance in Rail Transportation: An Explainable Machine Learning Approach - Mabaso, Nelisa Zamantungwa Sphumelele (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.